Konsep Edukratif pada Mebel Anak-anak di Taman Bacaan Masyarakat dan PAUD di Area Eks. Lokalisasi Dolly Surabaya - Ivonne Sugianto; Mariana Wibowo; Filipus Priyo Suprobo (Intra, 2019)
The Dolly Alleyway in Putat Jaya is a well-known area in Surabaya with a history for Commercial Sex Worker (CSW) doing commercial sex, so the government closes the Dolly alley and build a Society Reading Community (SRC) and Early Childhood Education (ECE) for the advancement of children in.Society Reading Community exist as a place to read, and reading is one of the main factor that effect a nation’s development, which is why it is essential to be nurtured since early age. However, some ECE’s children in Dolly rarely visit Society Reading Community. Therefore we need an interesting furniture for children to visit. So from that needed furniture that is attractive for children to want to visit. There are two ways that are used to check reading interest and that is interest in reading activities with books and approaches to interesting objects, so that furniture with interactive approach is needed. Asides from reading, other skills are needed with participating in learning activities, one of them is Early Childhood Education. Because of Society Reading Community and ECE in the Dolly area took place in one building with a narrow room and lack of storage as well as other furniture, using 6 stages of Design Thinking can help in the process of designing the furniture. The output of the furniture has an “Edukratif” concept that can become a storage, bookshelves, chairs, tables and also provide interaction with the children.